Influence of Constant Temperature on Reproductive Parameters of Holotrichia oblita (Coleoptera: Scarabaeidae). Issue 1 (8th July 2015) - Chen, Haoliang; Lin, Lulu; Xie, Minghui; Zhang, Guangling; Su, Weihua
Abstract : Holotrichia oblita Faldermann (Coleoptera: Scarabaeidae) is a major pest both in field crops and forests because the larvae could eat the roots of most crops in the field, and the adults damage the leaves of trees and field crops. In this study, we focused on the effects of temperature on H. oblita reproductive parameters. The results indicated H. oblita female adults at 25°C could lay more eggs (84.0 eggs per female) and have the shortest preoviposition period (19.1 d), the greatest oviposition rate (2.8 eggs per female per 3 d), and largest percentage of life span spent in oviposition (59.5%). The longevity and the time to 50% egg laying decreased with increasing temperature, and female longevity was always longer than male longevity. The preoviposition and postoviposition period decreased with increasing temperature from 15 to 25°C and then increased when the temperature increased from 25 to 30°C. These results show that 25°C is the optimal temperature for reproduction of H. oblita .